Protein Phosphatase 1 Regulatory Subunit 3C integrates cholesterol metabolism and isocitrate dehydrogenase in chondrocytes and neoplasia - Makoto Nakagawa; Eijiro Shimada; Nicholas Guardino; Ryo Miyamoto; Vijitha Puviindran; Emily Peairs; Ariana Matarangas; Koji Ishikawa; Tuyet Nguyen; Makenna Browne; Choiselle Marius; Asjah Wallace; et al. (Proceedings of the National Academy of Sciences, 2025)
Enchondromas are common bone tumors composed of chondrocytes originating from growth plate cells which can progress to malignant chondrosarcoma. Mutations in the genes encoding isocitrate dehydrogenase (IDH1 and IDH2) are identified in a large proportion of these tumors. IDH enzymes convert isocitrate to alpha-ketoglutarate (α-KG), an essential component of the citric acid cycle. While mutant IDH enzymes produce 2-hydroxyglutarate, which has epigenetic effects important in tumor initiation, cell maintenance and growth rely on additional factors. Prior work shows that intracellular cholesterol and glycogen are upregulated in mutant IDH chondrocytes. Here, we show that Protein Phosphatase 1 Regulatory Subunit 3C (PPP1R3C, previously termed Protein Targeting to Glycogen or PTG) is highly expressed in chondrocytes harboring a mutant IDH. Furthermore, Sterol Regulatory Element-Binding Proteins (SREBPs), transcriptional regulators of sterol biosynthesis, regulate PPP1R3C expression. We found that PPP1R3C regulates glycolysis and glycolytic capacity in chondrocytes. Depletion of PPP1R3C in mouse chondrocytes in vivo suppresses the neoplastic phenotype. The growth plate phenotype associated with the genetic inhibition of cholesterol biosynthesis is partially rescued by PPP1R3C overexpression. Taken together, our data show that PPP1R3C integrates cholesterol metabolism and isocitrate dehydrogenase in growth plate and neoplastic chondrocyte metabolism by regulating intracellular glycogen levels.